1998
DOI: 10.1182/blood.v91.4.1206
|View full text |Cite
|
Sign up to set email alerts
|

Thrombopoietin, kit Ligand, and flk2/flt3 Ligand Together Induce Increased Numbers of Primitive Hematopoietic Progenitors From Human CD34+Thy-1+Lin− Cells With Preserved Ability to Engraft SCID-hu Bone

Abstract: CD34+Thy-1+Lin− cells are enriched for primitive hematopoietic progenitor cells (PHP), as defined by the cobblestone area-forming cell (CAFC) assay, and for bone marrow (BM) repopulating hematopoietic stem cells (HSC), as defined by the in vivo SCID-hu bone assay. We evaluated the effects of different cytokine combinations on BM-derived PKH26-labeled CD34+Thy-1+Lin− cells in 6-day stroma-free cultures. Nearly all (>95%) of the CD34+Thy-1+Lin− cells divided by day 6 when cultured in thrombopoietin (TPO), c-k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
45
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(49 citation statements)
references
References 37 publications
4
45
0
Order By: Relevance
“…Candidate HSCs have been characterized as CD34 + CD38 À and further subclassified based on the presence or absence of HLA-DR and Thy-1(CDw90) or on efflux of Rhodamine-123 dye and other dyes. Several investigators have reported that a subset of adult CD34 + bone marrow (BM) cells expresses Thy-1 antigen and that the CD34 + Thy-1 + subset also contains most longterm culture-initiating cells and cobble-stone areaforming cells [8][9][10][11][12][13][14]. Thus, the Thy-1 + subset among HSCs might represent valuable target cells for gene transfer.…”
Section: Introductionmentioning
confidence: 99%
“…Candidate HSCs have been characterized as CD34 + CD38 À and further subclassified based on the presence or absence of HLA-DR and Thy-1(CDw90) or on efflux of Rhodamine-123 dye and other dyes. Several investigators have reported that a subset of adult CD34 + bone marrow (BM) cells expresses Thy-1 antigen and that the CD34 + Thy-1 + subset also contains most longterm culture-initiating cells and cobble-stone areaforming cells [8][9][10][11][12][13][14]. Thus, the Thy-1 + subset among HSCs might represent valuable target cells for gene transfer.…”
Section: Introductionmentioning
confidence: 99%
“…Clinically transplantable hematopoietic stem cells (HSC) should prove to have a long-term repopulating ability. Until recently, most of the human HSC studies aimed at clinical application have used in vitro assays for CD34 + cells, colonyforming cells in clonal culture, cobblestone area-forming cells, and long-term culture-initiating cells [1][2][3][4][5], but these surrogate assays have been shown not to correctly reflect stem cell activity. However, the recent development of assays measuring the ability to reconstitute human hematopoiesis in ontologically or genetically immunodeficient animals has enabled investigators to evaluate the stem cell activity [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…It is likely that synergistic cytokines induce distinct survival-signaling pathways. Previous studies have indicated that KL and FL have synergistic properties that lead to increased survival in human and mouse stem cells and early progenitors [6,7,[37][38][39]. The results offer an appealing explanation to these mechanisms.…”
Section: Discussionmentioning
confidence: 87%
“…To maintain the immature pool of stem cells and progenitors, mechanisms must be activated that suppress apoptosis and permit the cells to respond to other signals for further maturation. Several studies have indicated that certain cytokines are essential to promote survival, including kit ligand (KL; also stem cell factor or steel factor), flt3 ligand (FL), thrombopoietin (Tpo), interleukin-3 (IL-3), IL-6, and IL-11 [1][2][3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%